S60 Omalizumab in children can reduce asthma emergency department presentations: retrospective real-world uk data. (15th November 2017) - Murray, CS; Raymond, B
Abstract : Introduction and Objectives: Omalizumab is indicated as add-on therapy to improve asthma control in children aged ≥6 years with severe persistent allergic asthma. 1 In the UK, only children with the most severe allergic asthma phenotype are eligible for treatment with omalizumab (as an add-on to optimised standard therapy and who need continuous or frequent (≥ 4 courses/year) treatment with oral corticosteroids. 2 However, published clinical trials tell us little about the likely benefit in this cohort. Real-world studies have been shown to complement Results from clinical trials and have been published with regard to omalizumab in adults. Using real-life data, we aimed to investigate whether emergency department (ED) attendances were reduced in children following the use of omalizumab. Methods: Using Hospital Episode Statistics data from hospitals in England, we examined ED attendance data for children aged 6–16 years who received omalizumab. Children who had received their first dose of omalizumab between 01/01/2011 and 31/12/2013 were included and had asthma related ED activity extracted for the 24 months prior to the date of the first omalizumab injection, and for the subsequent 24 months. Children who had not received a minimum of 24 injections in the subsequent 24 months were excluded from the analysis. Results: 192 children (mean age 12.9 years) received their first injection of omalizumab between 01/01/2011 and 31/12/2013, of which 54 children received a minimum of 24 injections and were included in the analysis. There was a significant reduction in the number of children with ED attendances over the 24 months of omalizumab injections compared with the 24 months prior to starting treatment (p=0.001; figure 1 ). Also, children had significantly fewer ED attendances during the autumn in the 2 years whilst receiving omalizumab than in the 2 years prior to treatment (p=0.001). Conclusions: Although omalizumab in the UK is generally prescribed to children with more severe allergic asthma than those children who have been included in clinical trials, real-world paediatric data appears to complement clinical trial data, suggesting omalizumab reduces ED attendances in children with severe allergic asthma. References: Omalizumab SmPC. https://www.medicines.org.uk/emc/medicine/24912 NICE Guidance 278 . https://www.nice.org.uk/guidance/ta278